A Modified Class-Eπ1b For Capacitive Power Transfer System - Md Saat, Mohd Shakir; Yusop, Yusmarnita; Abd Ghani, Zamre; Husin, Siti Huzaimah; Rahman, F.K.A. (Penerbit Universiti, UTeM, 2017)
This paper exhibits the advancement of another power transfer method utilizing electric field as energy medium transfer, namely capacitive power transfer. Capacitive power transfer system has been introduced as an attractive alternative to the traditional inductive coupling method due to better electromagnetic interference performance and robustness to surrounding metallic elements. In this work, a Class-E inverter has been utilized to drive the proposed CPT system. However, the Class-E inverter is highly sensitive to its circuit parameters under the scenario of having small capacitance at the coupling plate. As a solution, a 1b matching type has been integrated with Class-E inverter to provide impedance transformation and increase coupling capacitance for a better performance. The validity of the proposed idea has been approved through a 10W experimental work. The performance of the proposed topology is broke down in term of zero voltage switching and DC-DC effectiveness. Experimental work has successfully demonstrated that the proposed system able to transfer 8.82W of power across the 1.82nF capacitive interface, operating frequency of 1MHz, with 91.2% efficiency at 0.25mm working distance.